Estrategias de marketing en la Empresa Todo Wow de la ciudad de Babahoyo, en el periodo 2023. - Quinto Amaiquema, Maoly Gissel (2024)
Despite the difficult market conditions for plastic products, the TODO WOW company has implemented an effective and well-structured marketing plan. After examining the 8 P's of marketing, which are product, price, place, advertising, promotion, process, personnel, productivity and quality, strategies have been established to achieve the stated objectives. Financial reporting involves implementing a predefined strategy and making future projections about the advertising budget and percentage of sales. When proposing and executing marketing strategies, some of them offer significant advantages to TODO WOW without requiring substantial financial resources or technological advances. It is also recommended to continue with the other suggested approaches, as well as always remembering that engaged staff members are more effective.